Prevalence and diversity of small rodent-associated Bartonella species in Shangdang Basin, China. - Juan Yu; Bing Xie; Ge-Yue Bi; Hui-Hui Zuo; Xia-Yan Du; Li-Fang Bi; Dong-Mei Li; Hua-Xiang Rao (Public Library of Science (PLoS), 2022)
The aim of this study was to investigate the occurrence and molecular characteristics of Bartonella infections in small rodents in the Shangdang Basin, China. Small rodents were captured using snap traps, and their liver, spleen, and kidney tissues were harvested for Bartonella detection and identification using a combination of real-time PCR of the ssrA gene (296 bp) and conventional PCR and sequencing of the gltA gene (379 bp). Results showed that 55 of 147 small rodents to be positive for Bartonella, with a positivity rate of 37.41%, and 95% confidence interval of 29.50%- 45.33%. While the positivity rate across genders (42.62% in males and 33.72% in females, χ2 = 1.208, P = 0.272) and tissues (28.57% in liver, 33.59% in spleen, and 36.76% in kidney, χ2 = 2.197, P = 0.333) of small rodents was not statistically different, that in different habitats (5.13% in villages, 84.44% in forests, and 54.17% in farmlands, χ2 = 80.105, P<0.001) was statistically different. There were 42 Bartonella sequences identified in six species, including 30 B. grahamii, three B. phoceensis, two B. japonica, two B. queenslandensis, one B. fuyuanensis and four unknown Bartonella species from Niviventer confucianus, Apodemus agrarius and Tscherskia triton. In addition to habitat, Bartonella species infection could be affected by the rodent species as well. Among the Bartonella species detected in this area, B. grahamii was the dominant epidemic species (accounting for 71.43%). B. grahamii exhibited four distinct clusters, and showed a certain host specificity. In addition, 11 haplotypes of B. grahamii were observed using DNASP 6.12.03, among which nine haplotypes were novel. Overall, high occurrence and genetic diversity of Bartonella were observed among small rodents in the Shangdang Basin; this information could potentially help the prevention and control of rodent-Bartonella species in this area.